Gagones A–F: Six prenylated chalcones from the heartwood of Mansonia gagei. (February 2023) - Le, Huong Thi Thu; Nguyen, Lam H.; Nguyen, Tuan H.; Nguyen, Van-Kieu; Danova, Ade; Truong, Thanh N.; Chavasiri, Warinthorn
Abstract: Six undescribed prenylated chalcones gagones A–F were isolated from the acetone fraction of Mansonia gagei heartwood. Their structures were unambiguously established based on spectroscopic analysis (HRESIMS, 1D and 2D NMR), as well as comparison to literature data. Their absolute configurations were elucidated using DP4 and electronic circular dichroism calculations. Isolated compounds were evaluated for their inhibitory activity against α-glucosidase and DPPH assay. All of the tested compounds exhibited better activity than that of acarbose (IC50 93.6 ± 0.5 μM). Among them, gagone D exhibited the highest α-glucosidase inhibitory with the IC50 value of 3.6 ± 0.4 μM. For antioxidant activity, gagones A–C, and E showed more active than that of ascorbic acid (IC50 30.2 ± 0.5 μM) with the IC50 values of 13.2 ± 0.7, 20.1 ± 0.4, 19.3 ± 0.5 and 12.8 ± 0.2 μM, respectively. Graphical abstract: Six undescribed prenylated chalcones have been isolated from the acetone fraction of Mansonia gagei heartwood. Some isolated chalcones significantly exhibited α-glucosidase inhibitory activity and antioxidant activity. Image 1 Highlights: Six undescribed chalcones were isolated from the acetone fraction of Mansonia gagei heartwood. The stereochemistry was determined by using DP4 protocol and ECD calculations. Their antioxidant and α-glucosidase activities were evaluated.